Reevaluating the safety of chamomile poultices in ophthalmic care - Rák, Tibor; Csutak, Adrienne (Frontiers in Pharmacology, 2025)
IntroductionGerman chamomile [Matricaria recutita L. (Asteraceae)] tea poultices are a common folk remedy in Central and Eastern Europe for treating eye inflammations such as blepharitis and conjunctivitis. This practice often precedes medical consultation and professional advice. Surprisingly, some healthcare professionals, including pharmacists, naturopaths, general practitioners, and pediatricians, recommend it as a primary treatment, particularly among the elderly. However, the ophthalmic use of chamomile lacks scientific validation, and the European Medicines Agency (EMA) and ophthalmic guidelines warn of potential allergic reactions, including life-threatening anaphylaxis.MethodsThis review examines the origins and descriptions of herbal poultices, with a focus on chamomile, by analyzing data from Hungarian and international medical literature. The study highlights the unsanitary production and storage conditions, also the external application of chamomile teas, which increase the risk of infection and contamination.ResultsThe findings indicate that chamomile tea poultices pose significant health risks due to potential allergic reactions and microbiological contamination. The study underscores the lack of scientific evidence supporting the ophthalmic use of chamomile and the dangers associated with its application.DiscussionThe implications of these findings are critical for healthcare professionals and guideline developers. The study calls for discontinuing chamomile-based ophthalmic therapies and emphasizes the need for evidence-based practices. Future research should focus on validating the safety and efficacy of herbal remedies and developing guidelines to protect public health.